Глава 13. Оптимальна модель провадження у справах про встановлення фактів, що мають юридичне значення, в цивільному судочинстві України: нові виклики для правозастосовчої практики в умовах військової агресії в Україні починаючи з 2014 року - Угриновська, Оксана Іванівна; Віцькар, Анастасія Сергіївна (Цивільний процес: теорія і практика. Концепції вчених з удосконалення законодавства про цивільне судочинство. Монографія, 2023)
Abstract. The scientific study is dedicated to the study of the pecu liarities of establishing legal facts in the conditions of the military aggression of the Russian Federation against Ukraine (since 2014), as well as the limits of the court’s discretionary powers in this area. The authors, within the framework of this theoretical and applied work, while delineating the limits of the court’s discretionary powers, singled out the general conditions for establishing a legal fact in the order of civil jurisdiction, classified legal facts related to military aggression in Ukraine according to the order of establishment, and also carried out a detailed comparative analysis of the revisions of Article 317 of the Civil Code of Ukraine, which underwent significant changes in connection with the adoption by the Verkhovna Rada of Ukraine on July 1, 2022 of Law of Ukraine № 2345-IX «On Amendments to Certain Legislative Acts of Ukraine Regarding the Peculiarities of Proceedings in Cases Establishing the Fact of Birth or Death of a Person in conditions of war or state of emergency and in temporarily occupied territories». A legal evaluation of these changes was given and their effectiveness was analyzed taking into account the already formed judicial practice. Peculiarities of the Georgian and Moldovan models of establishing the facts of the death/birth of a person in the temporarily occupied territory are singled out, since in the past Georgia and Moldova, like Ukraine, were «lucky» to experience the «care of a brotherly neighbor». Taking into account the military realities in Ukraine and the prevailing circumstances, an opinion is expressed as to whether it is possible to introduce features of the Moldovan and/or Georgian models in Ukraine.The purpose of the study is to outline the limits of the court’s discretionary powers regarding the establishment of legal facts in the conditions of the military aggression of the Russian Federation against Ukraine (since 2014). Isolation of the general conditions for the establishment of a legal fact in the procedure of civil jurisdiction. Taking into account the specific conditions and on the basis of the study of the judicial practice of the Unified State Register of Court Decisions, the classification of legal facts related to military aggression in Ukraine, according to the order of establishment. Analysis of key legislative changes made to the provisions of the Civil Procedure Code in terms of simplifying the procedure for establishing the fact of birth and death of a person in the temporarily occupied territory, under conditions of war and state of emergency. As well as a comparison of the relevant versions of Article 317 of the Civil Code of Ukraine to provide a legal assessment of the effectiveness of the changes made. Highlighting the key features of the Georgian and Moldovan models of establishing the fact of birth and death of a person in the temporarily occupied territory with the possibility of further borrowing and adoption of experience, as well as the implementation of such in Ukraine.Research methodology. The method of system analysis and compa rison was used during the research.Analysis of recent research and publications. A qualitative description of separate proceedings as an institution of civil procedural law is given in the works of M. M. Yasynok, O. O. Markova, V. Yu. Mamnytskyi, T. M. Balyuk, Y. M. Sadikova, Yu. V. Bilousov. The scientific works of A. V. Kostruba, K. I. Hychka, G. V. Kykot, V. V. Masyuk, and V. V. Komarov are devoted to the issue of establishing facts that have legal significance in separate proceedings under the Code of Civil Procedure of Ukraine. In addition, the study of the relevance of the indicated issues proves that the problems of legal regulation of the procedure for establishing the fact of birth and death of a person in the temporarily occupied territory of Ukraine are not fully studied. Although it is worth noting the significant contribution to research in this area by K. V. Husarova, I. M. Volkova, T. A. Stoyanova, M. H. Sviderska, O. I. Ugrynovska. and Pinyashka M., as well as other specialists in the science of civil procedural law. The empirical basis of primary source research is the modern legislation of Ukraine, as well as the legislation of Georgia and Moldova.In addition, it should be noted that M. Basilashvili covered the issue of comparative legal analysis of registration of civil status acts in Ukraine and Georgia in her research.Conclusions. It is obvious that cases on the establishment of facts of legal significance occupy an important place in judicial practice. The dynamism of social relations, and therefore the constant change of legislation in the conditions of war (since 2014), made it necessary to establish a new type of legal facts – a legal fact related to military aggression in Ukraine. The study of judicial practice on this issue gives reason to assert that the judicial body’s approach to the consideration of the specified category is becoming more and more qualitative. Aspecial role in the formation of the unity of judicial practice in solving the issue of establishing legal facts related to military aggression in Ukraine is played by the Supreme Court, which always stands guard to protect the violated rights of individuals. The legislative changes analyzed in this scientific study in terms of simplifying proceedings in cases of establishing the fact of birth or death of a person in the territory where a state of war or emergency has been imposed, or in the temporarily occupied territory of Ukraine, can rightly be called progressive, appropriate and necessary, since such are dictated by the realities of wartime in our country. Moreover, they will contribute to the unification of judicial practice in the matter of establishing the fact of birth and death of a person in the territory where a state of war or emergency has been imposed, or in the temporarily occupied territory of Ukraine. But the legislator still has a lot to work on in this matter. The regulation of the institution of establishing the fact of birth and death of a person in the temporarily occupied territory in Georgia and Moldova has many features, original legal norms that give grounds to conclude about the possibility of implementing specific positive points of foreign models of establishing the specified types of legal facts in Ukraine by improving Ukrainian legislation and applying in the Ukrainian legal space.